Aplikasi Game Edukasi Ilmu Pengetahuan Alam - Febri Haswan, Nofri Wandi Al-Hafiz (RJOCS (Riau Journal of Computer Science), 2017)
Lesson natural science with the discussion of the transportation system and the respiratory system, excretory system, the sense of hearing and sonar systems, light and optical instruments, the solar system and life on Earth, is to see and understand in textbooks alone (LKS), books used is the book Natural Sciences Curriculum 2013. the problem that often arises is the textbook used easily torn or are not durable and lack of interest in learning the studentsindependently and prices of books are more expensive. To overcome these problems, SMPN 4 Teluk Kuantan require a breakthrough in the process of learning to use the "LessonsEducational Game App Natural Sciences". This educational game provides about the subject matter and the evaluation questions science curriculum in 2013 semesters 2. We make natural science educational game that is interactive, make students more interested in learning the lessons of natural science and can stimulate and trigger fascination dents students to learn science to support learning at school and at home.